Perkembangan Moral Anak dalam Prespektif Sigmund Freud - Tanjung, Dewa Farizal; Priyati, Olivia Prisca Ari; Firmansyah, Reza April (FKIP Universitas Islam Jember, 2023)
This literature review examines the psychoanalytic theory founded by Sigmund Freud, one of the well-known forms of discussion is that the personality structure consists of: id, ego, and superego. The id and superego are both described as the subconscious of the individual. If the id is the same as the ego, then it is certain that the superego is not functioning and a child cannot be said to have good morals. If the ego is the same as the superego then a child can be sure to have good morals and character. Crime does not easily appear in children's behavior. The purpose of this paper is how we can grow the child's superego in Sigmund Freud's psychoanalytic theory. This study is related to psychoanalytic theory and educates about the moral personality of children